The Routledge handbook on climate crisis communication : community construction and creativity - Anderson, Alison, 1965-; Howarth, Candice (Routledge, 2025)
"This Handbook provides a state-of-the-art review of leading research on climate change communication. As climate change has moved further up the political agenda, the challenge of how to communicate the scientific, social, and political aspects of the climate emergency is of increasing interest to researchers, NGOs, governments, and policymakers at national and international levels. The Routledge Handbook on Climate Crisis Communication provides a concise and expert summary of this growing field, explaining the theoretical, conceptual, and empirical developments that have been made in recent years and describing the origins and connections to broader topics including: risk perception; environmental journalism; social media; and climate justice and activism. With contributions from leading international scholars, the book is divided into eight key parts: Part I: Introduction Part II: Conceptual Challenges Part III: Methodological Considerations Part IV: Communicating Climate Science across Cultures Part V: Journalism and News Reportage Part VI: Activism and Social Movements Part VII: Audiences and Popular Culture Part VIII: Future Directions Taking stock of the current landscape of climate change communication and helping to shape the field of inquiry going forward, this is a go-to guide for established and newly interested researchers, for government and policymaking bodies, and for students and their instructors"-- Provided by publisher.
Keywords: Climatic changes -- Press coverage.; Communication in science.; elektronické knihy; electronic books